Hungry for More: Measuring Metabolomic Responses in ANCA-Activated Monocytes - Leacy, Emma Julia (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Immunometabolism examines the links between immune cell function and their metabolism. Advances in liquid chromatography mass spectrometry (LC-MS) technologies have uncovered unique insights into cellular metabolomics. Dysregulation of immune cell metabolism is now an established feature of many autoimmune diseases. One such condition is anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV), where monocyte metabolism is disrupted following ANCA stimulation leading to pathogenic inflammation. In this thesis I have optimised LC-MS methods for metabolomic profiling of primary monocytes, and investigated the role of metabolism in response to ANCA stimulation. I first defined optimum cell culture conditions and experimental protocols for ANCA stimulation of primary monocytes. I then investigated ways to better combine immunologic and metabolic readouts in these cells. Flow cytometry, histology, ELISA, RT-qPCR, and western blots can all be completed in a single four-hour stimulation experiment alongside the core LC-MS analysis, but Seahorse investigations must be completed in parallel. Pilot investigations also uncovered changes in ANCA antigen expression with age and links to amino acid production via glycolysis. Next, I optimised sample preparation and LC-MS conditions for metabolomic profiling of these cells. A methanol-based metabolite extraction protocol was deemed most appropriate, and a Hydrophilic Interaction Liquid Chromatography (HILIC) LC-MS method provided excellent coverage of the monocyte metabolome. The analysis pipeline requires sample normalisation to account for technical and biological variation. I have validated measurement of the residual protein content of the metabolite fraction as a means of normalising primary cellular metabolomic data, and have optimised a commercial assay protocol for this purpose. Finally, these optimised experiments were completed in a cohort of healthy donor monocytes stimulated with ANCA. Alterations in several amino acids and several lipid species were discovered, with a greater effect seen in cells activated with anti-myeloperoxidase (MPO). Increases in several metabolites also appear to be linked to ANCA antigen expression. While the changes in cellular metabolism at this early (4 hour) timepoint are subtle, they do suggest a link between metabolic activation and upregulation of inflammatory responses. These data implicate changes in monocyte metabolism in the pathogenesis of AAV. This hypothesis-generating work should be further validated to determine the specific role of these metabolites in ANCA-induced inflammation. These metabolic pathways may also hold potential as therapeutic targets for AAV.
APPROVED
Keywords: ANCA-Associated Vasculitis; Metabolomics; Monocytes; LC-MS